PV system reactive power coordination with ULTC & shunt capacitors using grey wolf optimizer algorithm - Mogaligunta Sankaraiah; S Suresh Reddy; M Vijaya Kumar (Institute of Advanced Engineering and Science, 2020)
The presence of PV systems increases rapidly in distribution systems to improve reliability and quality of supply. This will influence the performance of under load tap changing (ULTC) transformer and related reactive power devices. Therefore, many researchers are working on this area. This paper main objective is to reduce switching operations of reactive power devices (ULTC and Shunt capacitors) together with system power loss. Distribution system load and solar system power will predict one day in advance and grey wolf optimizer (GWO) algorithm proposed to solve the objective function. Reactive power of solar system is coordinated together with ULTC and shunt capacitors (SCs) with the aid of forecasted load. Distribution system losses and switching operations of ULTC and SCs converted into objective function in terms of cost. The proposed method is applied on practical 10KV system and the results are compared with conventional and particle swarm optimization (PSO) methods considering grid conditions.